Succession from fluvial to aeolian environment recorded at westernmost part of the Wallachian basin, Serbia - Krsmanović, Petar; Radaković, Milica G.; Perić, Zoran ; 0000-0003-0116-8895; Thompson, Warren; Ryan, Cathal; Marković, Rastko S.; Pilipović, Aleksandar; Marković, Slobodan B. (NATURAL RESOURCES AND ENVIRONMENTAL RISKS: Towards a Sustainable Future, Novi Sad, Serbia, 2023-10-13 - 2023-10-15, 2023)
The Danube fluvial terrace in Velika Vrbica is situated at the westernmost edge of the Wallachian basin, Serbia. The profile is positioned in a gully valley with a base consisting of point bar sands interlayered with overbank clay deposits, which are together covered by loess sediments. The investigated loess-paleosol sequence (LPS) has a height of 11.15 m and has been sampled at 5 cm intervals for geochemical analysis using XRF. Fluvial sediments were sampled and analysed as well. Weathering indices such as Al/Sr, Rb/Sr and Zr/Sr for LPS clearly correlate with the first 5 MIS stages. Zr/Rb and Si/Al ratios were used as grain size proxies and they indicate that the largest sediment grain sizes correlate with the MIS 1 and MIS 2 stages. Chemistry of fluvial sediments was analysed in the context of loess provenance which was investigated using (Al/Ti)/(Fe/Ti) plot, principal components analysis, k-means clustering and discriminant analysis. Prior to analysing, the sediments were divided up in 5 groups: loess, paleosol, aeolian sand, point bar sands and overbank deposits. The results show that most of the chemical variability can be attributed to differences in grain size and different weathering intensities, which is furthermore illustrated by the fact that fluvial and aeolian sands are the groups which share the most similar chemical composition. Analysis showed that Zr concentrations are generally lower in fluvial sediments compared to aeolian, with loess containing more Zr than point bar sands which is contrary to what is expected, having in mind the properties of zircon (most abundant Zr-bearing mineral). This leads to a conclusion that Danube’s alluvium is not the only source for loess at Velika Vrbica and that low Zr concentrations for aeolian sand illustrate that it mostly originates from point bar sands which experienced aeolian transport before being deposited.